Paradigma Naturalistik dalam Penelitian Pendidikan: Pendekatan Kualitatif dan Penggunaannya - Parsudi Suparlan (Antropologi Indonesia, 1997)
This article discusses hoe the qualitative approach in the social sciences is applied to the study of education and educational systems. A discussion is given on how the qualitative approach differs from the quantitative approach, with an emphasis on how an understanding of the culture of the people under study becomes of a central importance in the former. Educational institutions must be studied within a wider context, allowing the researcher to identify relevant problem areas that are often deemed irrelevant by quantitative studies using deductive models. It is also noted that research conducted with the qualitative approach requires that the researcher must have sufficient theoretical and conceptual knowledge, as well as knowledge of the methods needed to collect data.